2018
DOI: 10.1111/1346-8138.14673
|View full text |Cite
|
Sign up to set email alerts
|

Indeterminate dendritic cell neoplasm accompanied by eosinophilic pneumonia successfully treated by systemic steroid therapy: Report of the first case with muscular and parotid involvement and review of published work

Abstract: A 34‐year‐old Japanese man presented with an indolent nodule on the right flank. Computed tomography of the chest and abdomen demonstrated a large nodule measuring 55 mm × 50 mm in the abdominal oblique muscle layer of the right flank, and several small nodules were seen in the muscle layer throughout the body and subcutaneous tissue of the lower abdomen. 18F‐fluorodeoxyglucose‐positron emission tomography/computed tomography revealed nodular lesions in the bilateral parotid glands, bilateral cervical lymph no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…We then selected and included in the study 78 papers, describing 108 patients (Figure 1). 5,8,9,12,32–106 From two case series, we included only some of the described patients, as indicated in Table 1 12,48 …”
Section: Resultsmentioning
confidence: 99%
“…We then selected and included in the study 78 papers, describing 108 patients (Figure 1). 5,8,9,12,32–106 From two case series, we included only some of the described patients, as indicated in Table 1 12,48 …”
Section: Resultsmentioning
confidence: 99%
“…A recent review reported that most patients with IDCT exhibit various papules or nodules in the skin[ 8 ]. IDCT can occur directly in other organs, including the spleen[ 5 ], pancreas[ 6 ], thoracic spine[ 9 ], muscle[ 10 ] and bile duct. IDCT can imitate other diseases, and therefore, the diagnosis of IDCT patients with abdominal lesions may be delayed.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly, IDCT is restricted to the skin or lymph nodes. Other manifestations are extremely rare, with only three cases found in our literature search, including one case in the spleen, one in the spine and one in muscle and parotid [ 3 , 4 , 5 ]. To our knowledge, this is the first reported manifestation of IDCT in the pancreas.…”
Section: Discussionmentioning
confidence: 99%